Fracture Behaviour of Binary Styrene/Butadiene Block Copolymer Blends - Adhikari, R.; Lach, R.; Michler, G. H. (Journal of Nepal Chemical Society, 2007)
Morphology and fracture behavior of binary block copolymer blends (triblock and star block copolymers being made up of styrene and butadiene) have been studied via transmission electron microscopy (TEM) and instrumented Charpy impact testing. The toughness of the ductile blends has been characterized by dynamic crack resistance curves (R-curves). The lamellar star block copolymer shows nearly elastic behavior of small scale yielding and unstable crack growth. Addition of 20 wt % of a triblock copolymer comprising polystyrene domains dispersed in rubbery matrix leads to a strong increase in toughness. The mechanism of toughness modification, based on the nanophase-separated structures, represents a specific morphology-toughness correlation which differs fundamentally from toughening mechanisms observed in conventional polymer blends. DOI: 10.3126/jncs.v22i0.523 Journal of Nepal Chemical Society Vol. 22, 2007, pp. 55-66